If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3m + 5 = 2 Reorder the terms: 5 + -3m = 2 Solving 5 + -3m = 2 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -3m = 2 + -5 Combine like terms: 5 + -5 = 0 0 + -3m = 2 + -5 -3m = 2 + -5 Combine like terms: 2 + -5 = -3 -3m = -3 Divide each side by '-3'. m = 1 Simplifying m = 1
| k/7-3=2 | | 16+24c=22.5 | | C(h)=200+59.95h | | -32+17x=17x | | -100x=7 | | 1/3y-2=-8 | | 8z+7=95 | | 3x-15=-16 | | -4(n+3)=-3(n+4) | | (2a^-2b^2/10ab)^-2 | | 6c^2-8c= | | f(x)=5-6x^2 | | fA(x)=5-6x^2 | | 2x-3y-6z= | | 53=17+6c | | -6q+8=-82 | | 110=38.98+0.25x | | -2u+17=-23 | | 6=-2(10n+2) | | 5x/6-1/3=x-3/2 | | 16a^2+32ab= | | -37=-19 | | -8b+16=48 | | 13=2u+3 | | h/8-1=2 | | 32x+6= | | -7(-2v-8)=6(v+4) | | -9x+1=145 | | 8u+7=95 | | -5/7y-3=x | | q/8--40=50 | | -1/3x-3=y |